2014
DOI: 10.1007/s10459-014-9547-z
|View full text |Cite
|
Sign up to set email alerts
|

Examiners and content and site: Oh My! A national organization’s investigation of score variation in large-scale performance assessments

Abstract: Examiner effects and content specificity are two well known sources of construct irrelevant variance that present great challenges in performance-based assessments. National medical organizations that are responsible for large-scale performance based assessments experience an additional challenge as they are responsible for administering qualification examinations to physician candidates at several locations and institutions. This study explores the impact of site location as a source of score variation in a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 22 publications
(34 reference statements)
2
24
0
Order By: Relevance
“…Moreover, adjusting for examiner variance altered the pass/fail decisions of 11% of students in their study. Other studies have suggested that examiners' scores may be biased depending on the timing of OSCEs (Hope & Cameron, 2015;McLaughlin, Ainslie, Coderre, Wright, & Violato, 2009), the performance of other candidates (Yeates, Moreau, & Eva, 2015) or by different geographical locations (Sebok, Roy, Klinger, & De Champlain, 2015). Consequently, it is not sufficient to simply conduct an OSCE, and believe that the resulting scores are a fair representation of students' performance given the known influences of construct irrelevant variance.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, adjusting for examiner variance altered the pass/fail decisions of 11% of students in their study. Other studies have suggested that examiners' scores may be biased depending on the timing of OSCEs (Hope & Cameron, 2015;McLaughlin, Ainslie, Coderre, Wright, & Violato, 2009), the performance of other candidates (Yeates, Moreau, & Eva, 2015) or by different geographical locations (Sebok, Roy, Klinger, & De Champlain, 2015). Consequently, it is not sufficient to simply conduct an OSCE, and believe that the resulting scores are a fair representation of students' performance given the known influences of construct irrelevant variance.…”
Section: Introductionmentioning
confidence: 99%
“…Although examiner differences exist and can contribute to construct-irrelevant variance within an examination, their variability as a group remains relatively consistent over time. 23 Based on the generalizability study, the comparatively similar estimates of the error variances due to examiner effects between the two years led us to believe that no systematic differences in examiners existed across cohorts.…”
Section: Discussionmentioning
confidence: 98%
“…Examples include use of item fit analysis to test for variability in item difficulty across schools or styles of test administration [29,30] and for evidence of unidimensionality in the scores forthcoming from a test of clinical competence. [31] Further examples include testing for rater leniency or harshness as determinants of student performance.…”
Section: Rasch Analysis In Contemporary Medical Educationmentioning
confidence: 99%
“…[31] Further examples include testing for rater leniency or harshness as determinants of student performance. [32,33] In some of the above cases, [30] …”
Section: Rasch Analysis In Contemporary Medical Educationmentioning
confidence: 99%